Math, asked by hv0310716, 5 months ago

In each of the Exercise 1 to 10, show that the given differential equation is homogeneous and solve :-

 \sf {(x^2\ +\ xy)dy\ =\ (x^2\ +\ y^2)dx}

Answers

Answered by INSIDI0US
91

Step-by-step explanation:

Question :-

In each of the Exercise 1 to 10, show that the given differential equation is homogeneous and solve :-

 \sf {(x^2\ +\ xy)dy\ =\ (x^2\ +\ y^2)dx}

Solution :-

 \rm \circ\ {Step\ 1\ :\ Find\ \dfrac{dy}{dx}}

 : \implies {(x^2\ +\ xy)dy\ =\ (x^2\ +\ y^2)dx}

 {: \implies \dfrac{dy}{dx}\ =\ \dfrac{x^2\ +\ y^2}{x^2\ +\ xy}\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: -\ -\ -\ -\ -\ -\ (1)}

 \rm \circ\ {Step\ 2\ :\ Putting\ F(x,\ y)\ =\ \dfrac{dy}{dx}\ and\ finding\ F( \lambda x,\ \lambda y)}

 : \implies {F(x,\ y)\ =\ \dfrac{x^2\ +\ y^2}{x^2\ +\ xy}}

Finding F(λx, λy) :-

 {: \implies F( \lambda x,\ \lambda y)\ =\ \dfrac{( \lambda x)^2\ +\ ( \lambda y)^2}{( \lambda x)^2\ +\ \lambda x\ +\ \lambda y}}

 : \implies {\dfrac{ \lambda^2 x^2\ +\ \lambda^2 y^2}{ \lambda^2 x^2\ +\ \lambda^2 xy}}

 : \implies {\dfrac{ \lambda^2 (x^2 y^2)}{ \lambda^2 (x^2\ +\ xy)}}

 : \implies {\dfrac{x^2 y^2}{x^2\ +\ xy}}

 : \implies {F(x,\ y)}

 {So,\ F( \lambda x,\ \lambda y)\ =\ F(x,\ y)}

 : \implies { \lambda^0\ F(x,\ y)}

Thus, F(x,y) is a homogeneous equation function of order zero.

 \mathrm {Therefore,\ \dfrac{dy}{dx}\ is\ a\ homogeneous\ differential\ equation.}

 \rm \circ\ {Step\ 3\ :\ Solving\ \dfrac{dy}{dx}\ by\ putting\ y\ =\ vx}

Differentiating w.r.t.x :-

 : \implies {\dfrac{dy}{dx}\ =\ x \dfrac{dv}{dx}\ +\ v \dfrac{dx}{dx}}

 : \implies {\dfrac{dy}{dx}\ =\ x \dfrac{dv}{dx}\ +\ v}

 \rm {Putting\ value\ of\ \dfrac{dy}{dx}\ and\ y\ =\ vx\ in\ (1)\ :-}

 : \implies {\dfrac{dy}{dx}\ =\ \dfrac{x^2\ +\ y^2}{x^2\ +\ xy}}

 : \implies {x \dfrac{dy}{dx}\ +\ v\ =\ \dfrac{x^2\ +\ (vx)^2}{x^2\ +\ x(vx)}}

 : \implies {x \dfrac{dy}{dx}\ +\ v\ =\ \dfrac{x^2(1\ +\ v^2)}{x^2\ +\ x^2 v}}

 : \implies {x \dfrac{dy}{dx}\ +\ v\ =\ \dfrac{x^2(1\ +\ v^2)}{x^2(1\ +\ v)}}

 : \implies {x \dfrac{dy}{dx}\ +\ v\ =\ \dfrac{1\ +\ v^2}{1\ +\ v}}

 : \implies {x \dfrac{dy}{dx}\ =\ \dfrac{1\ +\ v^2\ -\ v\ -\ v^2}{1\ +\ v}}

 : \implies {x \dfrac{dy}{dx}\ =\ \dfrac{1\ -\ v}{1\ +\ v}}

 : \implies {\dfrac{(1\ +\ v)}{(1\ -\ v)}\ dv\ =\ \dfrac{dx}{x}}

 : \implies {- \bigg(\dfrac{v\ +\ 1}{v\ -\ 1} \bigg)\ dv\ =\ \dfrac{dx}{x}}

 : \implies {\bigg(\dfrac{v\ +\ 1}{v\ -\ 1} \bigg)\ dv\ =\ \dfrac{-dx}{x}}

By integrating both sides, we get :-

 {: \implies \displaystyle \int\ \bigg(\dfrac{v\ +\ 1}{v\ -\ 1} \bigg)\ dv\ =\ -\ \displaystyle \int\ \dfrac{dx}{x}}

 {: \implies \displaystyle \int\ \bigg(\dfrac{v\ +\ 1}{v\ -\ 1} \bigg)\ dv\ =\ -log \left|x \right|\ +\ c\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: -\ -\ -\ -\ -\ -\ (2)}

 : \implies {Let\ \bf I\ =\ \displaystyle \int\ \bigg(\dfrac{v\ +\ 1}{v\ -\ 1} \bigg)\ dv}

Now, solving I :-

 : \implies {I\ =\ \displaystyle \int\ \bigg(\dfrac{v\ +\ 1\ -\ 1\ +\ 1}{v\ -\ 1} \bigg)\ dv}

 : \implies {I\ =\ \displaystyle \int\ \bigg(\dfrac{v\ -\ 1\ +\ 2}{v\ -\ 1} \bigg)\ dv}

 : \implies {I\ =\ \displaystyle \int\ \bigg(\dfrac{v\ -\ 1}{v\ -\ 1}\ +\ \dfrac{2}{v\ -\ 1} \bigg)\ dv}

 : \implies {I\ =\ \displaystyle \int\ \bigg(1\ +\ \dfrac{2}{v\ -\ 1} \bigg)\ dv}

 : \implies {I\ =\ \displaystyle \int\ dv\ +\ \displaystyle \int\ \dfrac{2}{v\ -\ 1}\ dv}

 : \implies {I\ =\ \sf v\ +\ 2\ log \left|v\ -\ 1 \right|}

Now, putting v = y/x :-

 : \implies {I\ =\ \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{y}{x}\ -\ 1 \right|}

 : \implies {I\ =\ \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{y\ -\ x}{x} \right|}

Now, putting value of I in (2), we get :-

 {: \implies \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{y\ -\ x}{x} \right|\ =\ -\ log \left|x \right|\ +\ c}

 {: \implies \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{y\ -\ x}{x} \right|\ +\ log \left|x \right|\ =\ c}

 {: \implies \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{(y\ -\ x)^2}{x^2} \right|\ +\ log \left|x \right|\ =\ c\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (As\ a\ log\ b\ =\ log\ b^a)}

 {: \implies \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{(y\ -\ x)^2}{x}\ \times x \right|\ =\ c\: \: \: \: \: \: \: \: \: \: \: \: \: (As\ log\ a\ +\ log\ b\ =\ log\ ab)}

 {: \implies \dfrac{y}{x}\ +\ 2\ log \left| \dfrac{(y\ -\ x)^2}{x} \right|\ =\ c}

 {: \implies log \left| \dfrac{(y\ -\ x)^2}{x} \right|\ =\ c\ -\ \dfrac{y}{x}}

 {: \implies \dfrac{(y\ -\ x)^2}{x}\ =\ e^{c\ -\ \dfrac{y}{x}}}

 {: \implies \dfrac{(y\ -\ x)^2}{x}\ =\ e^c \times e^{- \dfrac{y}{x}}}

 {: \implies \dfrac{(y\ -\ x)^2}{x}\ =\ c\ e^{- \dfrac{y}{x}}}

 {: \implies (x\ -\ y)^2\ =\ cx\ e^{- \dfrac{y}{x}}}

Answered by Deetya1308
1

Answer:

the \: above \: answer \: is \: correct

Similar questions